Iqbal and Muslim ummah: concluding remarks (part seven) - Abdul Razak, Mohd Abbas (Mission Soft Foundation, 2023)
It was the brilliance of Iqbal, to capitalize on the use of poetry as a medium to express his ideas towards social reform because it was part of the culture of the people living in the subcontinent at that time to pass their leisure reading and listening to poetry in the media and in public gatherings. Iqbal’s works in the area of social and religious reforms are very much similar to what has been done by Imam Muhammad Abdul Wahhab (1703-1792), Al-Afghani (1838-1897), Syeikh Muhammad Abduh (1849-1905) and other great Muslim reformers in Islam. Propelled by the zeal to witness progress within the Islamic Ummah, Iqbal called for the banishment of all superstitious beliefs that were misleading the masses in the Islamic world, particularly in the subcontinent. By calling for the banishment of superstitious beliefs, he also called the Muslims to embark on the bandwagon of science, which promises progress. To Iqbal, Muslims living in the modern world must learn to adapt themselves by utilizing science but at the same time, they should not sever their relationship with the past Islamic heritage. In other words, Iqbal called the Muslims to interpret the Qur’an and Sunnah in the light of the scientific age in which they were living. He also believed that the failure on the part of Muslims to do so will be a state of stagnation and they would be left behind when compared to the others in the world, particularly the West. His exact words calling the Muslims to adapt to the ever-changing world were, “The task before the modern Muslim is, therefore, 2 immense. He has to rethink the whole system of Islam without completely breaking with the past” (Iqbal, 1996: 78).